Memorial dedicated to Henry Curwen - Ghosh, Ayan (2023)
Memorial plaque erected in memory of Henry Curwen (1845–1892), who died on 22nd Feb 1892, on board the P and O ship SS Ravenna, three days out of Mumbai. The vessel didn't return to port, and the body was buried at sea. Henry Curwen was born at Workington Hall in Cumbria and arrived in India in 1876 to work as a journalist. In 1880, he became the editor of the Times of India.